A Quantitative Golgi Study of Dendritic Morphology in the Mice Striatal Medium Spiny Neurons - Bicanic, Ivana; Hladnik, Ana; Petanjek, Zdravko (Frontiers in Neuroanatomy, 2017)
In this study we have provided a detailed quantitative morphological analysis of medium spiny neurons (MSNs) in the mice dorsal striatum and determined the consistency of values among three groups of animals obtained in different set of experiments. Dendritic trees of 162 Golgi Cox (FD Rapid GolgiStain Kit) impregnated MSNs from 15 adult C57BL/6 mice were 3-dimensionally reconstructed using Neurolucida software, and parameters of dendritic morphology have been compared among experimental groups. The parameters of length and branching pattern did not show statistically significant difference and were highly consistent among groups. The average neuronal soma surface was between 160 μm2 and 180 μm2, and the cells had 5–6 primary dendrites with close to 40 segments per neuron. Sholl analysis confirmed regular pattern of dendritic branching. The total length of dendrites was around 2100 μm with the average length of individual branching (intermediate) segment around 22 μm and for the terminal segment around 100 μm. Even though each experimental group underwent the same strictly defined protocol in tissue preparation and Golgi staining, we found inconsistency in dendritic volume and soma surface. These changes could be methodologically influenced during the Golgi procedure, although without affecting the dendritic length and tree complexity. Since the neuronal activity affects the dendritic thickness, it could not be excluded that observed volume inconsistency was related with functional states of neurons prior to animal sacrifice. Comprehensive analyses of tree complexity and dendritic length provided here could serve as an additional tool for understanding morphological variability in the most numerous neuronal population of the striatum. As reference values they could provide basic ground for comparisons with the results obtained in studies that use various models of genetically modified mice in explaining different pathological conditions that involve MSNs.